Bridges the crowd: rim chain framework. Issue 2 (30th August 2019) - Li, Pengze; Zhang, Ran; Liu, Lei; Cui, Lizhen; Li, Qingzhong; Zhou, Guangpeng
Abstract : Purpose: Science of the Crowd is a new paradigm. The research on the relationship between provision and requirement arising from the behavior of the crowd under the interconnected environment is a promising topic. This paper aims at studying a new type of interconnected architecture. Design/methodology/approach: This study is a pioneer work on the establishment of a new type of interconnected architecture – rim chain. The rim chain aims at supporting prompt matching between provision and requirements. Findings: The analytical results suggest that requirements can be fulfilled in accordance with six degrees of separation. In other words, the matching between the requirements and provision takes place with six hops in the rim chain framework. Originality/value: Knowledge graph is used to implement the rim chain.